Classifying pairs with trees for supervised biological network inference1. Issue 8 (14th August 2015) - Schrynemackers, Marie; Wehenkel, Louis; Babu, M. Madan; Geurts, Pierre
<x xml:space="preserve">Abstract</x> We systematically investigate, theoretically and empirically, the application of tree-based methods for the supervised inference of biological networks.